Evaluation of the innovation-investment factor for augmenting the competitiveness of construction enterprises - Nagdiev, O.; Нагдієв, О. А. (Харківський національний автомобільно-дорожній університет, 2023)
This article delves into the multifaceted realm of innovation and investment processes, shedding light on their intrinsic nature, economic ramifications, and pivotal roles in fostering resource efficiency. The study meticulously examines investment policies, delving into the imperative factors that drive investments in innovations, thereby necessitating the enhancement of management systems. The crux of the narrative emphasizes the profound significance of integrating innovations and investments to optimize resource utilization effectively. The exploration begins by scrutinizing the economic landscape during the initial years of the Republic of Azerbaijan's independence. It dissects the strategic steps taken to reconstruct the economy, highlighting the pivotal role played by state investment programmes. Special attention is devoted to the nuanced analysis of investments in the construction industry. This scrutiny extends to the impact of the landmark "Agreement of the Century" and the strategic development of the construction sector of Azerbaijan. Utilizing data from 1995 to 2021, the research analyzes the growth trends of fixed assets and investments in fixed capital in the construction sector. Despite a setback in 2020 due to the COVID-19 pandemic, the sector demonstrated resilience, rebounding in 2021. The findings reveal a substantial increase in both fixed assets and investments over the studied period, underscoring the sector's pivotal role in the country's economic development. The research recommends a dual-perspective consideration of innovation and investment activities – both as internal management processes and as fields for capital application for potential investors. The importance of effective dynamic management of investment needs and resources is emphasized, especially in the early stages of innovative projects. The study also explores the correlation between the share of construction in investments in fixed capital and the degree of economic openness in Azerbaijan. The article suggests the necessity of adapting the management structure of construction enterprises to innovation and investment activities, involving the creation of specialized units within construction enterprises. This extended exploration underscores the intricate relationship between innovation, investment, and economic dynamics, portraying them as symbiotic elements crucial for the sustainable growth of construction enterprises. The research contributes valuable insights into the economic dynamics of Azerbaijan's construction sector, offering recommendations for policymakers and industry stakeholders to foster sustained growth and competitiveness.
Оцінка інноваційно-інвестиційного фактора підвищення конкурентоспроможності будівельних підприємств
Keywords: investments; innovations; competitiveness; efficiency; innovative management; fixed assets; economic development; management system; construction enterprises; інвестиції; інновації; конкурентоспроможність; ефективність; інноваційне управління; основні засоби; економічний розвиток; система управління; будівельні підприємства; 658.512.2; 10.30977/ЕТК.2225-2304.2023.42.143